2007
DOI: 10.1152/ajpcell.00051.2007
|View full text |Cite
|
Sign up to set email alerts
|

nPKCε, a P2Y2-R downstream effector in regulated mucin secretion from airway goblet cells

Abstract: Ehre C, Zhu Y, Abdullah LH, Olsen J, Nakayama KI, Nakayama K, Messing RO, Davis CW. nPKCε, a P2Y 2-R downstream effector in regulated mucin secretion from airway goblet cells. Am J Physiol Cell Physiol 293: C1445-C1454, 2007. First published August 29, 2007; doi:10.1152/ajpcell.00051.2007.-Airway goblet cell mucin secretion is controlled by agonist activation of P2Y 2 purinoceptors, acting through Gq/PLC, inositol-1,4,5-trisphosphate (IP 3), diacylglycerol, Ca 2ϩ and protein kinase C (PKC). Previously, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…The use of retroviral infection vectors with SPOC1 cells, however, indicated that overexpression of cPKCα, nPKCδ, and nPKCη was without effect, whereas overexpression of nPKCε caused an increase in agonist-induced mucin secretion. Additionally, in perfused mouse tracheas the mucin secretory response to agonist was blunted in the nPKCε-deficient mouse, but not the nPKCδ-deficient mouse (48). Hence, nPKCε appears to be the isoform mediating agonist effects in goblet cells.…”
Section: Cellular Messengers In Purinergic Signalingmentioning
confidence: 90%
See 1 more Smart Citation
“…The use of retroviral infection vectors with SPOC1 cells, however, indicated that overexpression of cPKCα, nPKCδ, and nPKCη was without effect, whereas overexpression of nPKCε caused an increase in agonist-induced mucin secretion. Additionally, in perfused mouse tracheas the mucin secretory response to agonist was blunted in the nPKCε-deficient mouse, but not the nPKCδ-deficient mouse (48). Hence, nPKCε appears to be the isoform mediating agonist effects in goblet cells.…”
Section: Cellular Messengers In Purinergic Signalingmentioning
confidence: 90%
“…P2Y 2 -R was cloned from the airways (42) and appears to be the major purinoceptor regulating mucociliary clearance in the airways, including mucin release from goblet cells. ATP and UTP, the primary P2Y 2 -R agonists, elicit maximal secretion from goblet cells in all vertebrate species examined (e.g., see References 9 and 43), including human (44,45), the receptor mRNA has been identified in two goblet cell models (46,47), and the tracheal mucin secretory response to ATP is severely compromised in the P2Y 2 -R-deficient mouse (48).…”
Section: Receptor Activation Of Mucin Secretionmentioning
confidence: 99%
“…These bind to epithelial apical P2Y 2 receptors that activate G q , which in turn activates phospholipase C␤ 1 generating the intracellular second messengers diacylglycerol and inositol trisphosphate (IP 3 ). 3 Diacylglycerol directly induces mucin granule exocytosis by activating the priming protein Munc13-2 (4), and indirectly regulates exocytosis by activating protein kinase C⑀ (5). IP 3 induces the release of Ca 2ϩ from intracellular stores, resulting in a rise in cytoplasmic Ca 2ϩ that rapidly triggers mucin granule exocytosis (6 -9).…”
mentioning
confidence: 99%
“…These G␣ subunits share over 80% homology in their amino acid sequences (45), hence their ability to inhibit the channel might reflect a promiscuous capacity to activate the same downstream signaling pathways, one of which inhibits ENaC. Gq/11-coupled GPCRs are known to regulate several cellular events in epithelial cells, including intracellular Ca 2ϩ mobilization (46), mucin secretion (47,48), and anion secretion (49). Our data suggest that, Gq/11 plays a small, but significant, part in the P2Y 2 receptor-mediated signaling mechanism that inhibits activity of ENaC.…”
Section: Discussionmentioning
confidence: 99%